Study of the Experimental Conditions and Mechanisms for Diclofenac Loading in Functionalized Magnetic Nanoparticles - Agotegaray, Mariela Alejandra (2014)
Magnetic nanoparticles (MNPs) composed of magnetite coated with oleic acid and functionalized with chitosan have been prepared to the targeted release of the non steroidal anti-inflammatory drug (NSAID) Diclofenac. Two procedures to incorporate the drug were explored: simple adsorption and covalent linkage. The impact of experimental variables such as the nature of the NSAID (commercial versus analytical sodium Diclofenac), its concentration and amount of coupling agent were evaluated in terms of the loading efficiency and the properties of interest of MNPs (size, surface functionality, stability). Loaded and unloaded MNPs were characterized by FTIR-DRIFTS spectroscopy, dynamic light scattering, zeta potential and transmission electron microscopy. UV-visible quantification of Diclofenac was achieved reaching values of loading efficiency between 11 and 27% depending on the experimental conditions. Probable mechanisms for drug-MNPs interactions have been proposed on the base of characterization data. A nanocarrier of size lower than 150 nm, with satisfactory loading skill and high dispersion capability on water was obtained. The release behavior demonstrated to be independent on the presence of an external magnetic field. The properties found in these nanosystems result relevant in view of their effective in vivo implementation.